¿Hacia un urbanismo paracas en Ánimas Altas/Ánimas Bajas (valle de Ica)? - Bachir Bacha, Aïcha (2013)
Since 2009, within the framework of the Ánimas Altas Archaeological Program in Ica, Peru — under the direction of the au-thors — systematic excavations have been carried out in the Ánimas Altas/Ánimas Bajas archaeological complex, the center ofthe Paracas culture in the lower Ica valley. To date, the project has documented public-ceremonial architecture as well as domesticand production areas. Additionally, excavations have revealed evidence of pyramidal complexes contiguous to plazas, one smallpyramid housing an elite tomb decorated with a mural frieze, and remnants of dwellings and storage areas.In this article, we attempt to understand the function that Ánimas had during its prehispanic occupation, using data from recent excavations at the site. Our analysis draws on a wide range of material culture categories to facilitate reflections on the concepts of ‘city’ and ‘territory’ in the Andes, enriching our understanding of the process of prehispanic urbanism, a widely debated concept among Andeanists. Thus, we explore the meaning of the stylistic and technological heterogeneity observde in some types of materialamong Andeanists. Thus, we explore the meaning of the stylistic and technological heterogeneity observde in some types of materia culture, positing the idea that this heterogeneity reflects social and territorial dynamics, rather than mere diachronic variation.